2009
DOI: 10.1364/ao.48.000393
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gaussian laser beam radius using the knife-edge technique: improvement on data analysis

Abstract: We revisited the well known Khosrofian and Garetz inversion algorithm [Appl. Opt.22, 3406-3410 (1983)] that was developed to analyze data obtained by the application of the traveling knife-edge technique. We have analyzed the approximated fitting function that was used for adjusting their experimental data and have found that it is not optimized to work with a full range of the experimentally-measured data. We have numerically calculated a new set of coefficients, which makes the approximated function suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 15 publications
1
91
0
2
Order By: Relevance
“…Laser pulses of wavelength of 800 nm, duration of 60 fs, and energy in the range of 1.3-4.6 lJ (measured carefully with a power meter working in a single pulse mode) were focused at the sample surface with a lens. Determining the beam radius with the knife-edge method 19,20 showed that the spatial profile of the beam used in our experiment is fitted well with a sum of two Gaussian profiles. 21 The radii of both Gaussian components were equal to: r 1 ¼ (33.8 6 0.5)lm, r 2 ¼ (217 6 21)lm, with a dominant contribution of (98.6 6 0.4)% of the first one.…”
Section: Methodsmentioning
confidence: 67%
“…Laser pulses of wavelength of 800 nm, duration of 60 fs, and energy in the range of 1.3-4.6 lJ (measured carefully with a power meter working in a single pulse mode) were focused at the sample surface with a lens. Determining the beam radius with the knife-edge method 19,20 showed that the spatial profile of the beam used in our experiment is fitted well with a sum of two Gaussian profiles. 21 The radii of both Gaussian components were equal to: r 1 ¼ (33.8 6 0.5)lm, r 2 ¼ (217 6 21)lm, with a dominant contribution of (98.6 6 0.4)% of the first one.…”
Section: Methodsmentioning
confidence: 67%
“…Nesse trabalho, a determinação da largura do feixe foi feita num ponto indeterminado ao longo do eixo de propagação. A medida da largura do feixe pode ser feita por meio do método da lâmina [9,10], o qual consiste na quantificação da luz que atinge o detector como função da posição de uma lâmina queé deslocada perpendicularmenteà direção de propagação do feixe, por meio de um parafuso micrométrico. Para uma medida precisa, após a lâminaé posicionada uma lente a qual focaliza o feixe sobre o fotodetector.…”
Section: Materiais E Métodounclassified
“…the integral) of the beam is traced. Since the resulting trace does not replicate by itself the beam profile, a proper data inversion method needs to be used to finally obtain the beam intensity profile [19][20][21]. Figures 1(a) …”
Section: Knife-edge Technique For Spectral Measurementsmentioning
confidence: 99%